1998
DOI: 10.1046/j.1365-2591.1998.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological status of root-filled teeth with apical periodontitis

Abstract: The present study examined the microbiological status of 100 root-filled teeth with radiographically verified apical periodontitis--the pathology (P) group--and of 20 teeth without signs of periapical pathosis--the technical (T) group. In the P group 117 strains of bacteria were recovered in 68 teeth. In most of the cases examined one or two strains were found. Facultative anaerobic species predominated among these isolates (69% of identified strains). Growth was classified as 'sparse' or 'very sparse' in 53%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
576
8
54

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(663 citation statements)
references
References 0 publications
25
576
8
54
Order By: Relevance
“…Because of such a feature, they have been found associated with serious human infectious diseases, with increased morbidity and mortality (16,17). Pseudornonas and enterococci species have also been involved in some persistent and therapy-resistant endodontic infections (15,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Because of such a feature, they have been found associated with serious human infectious diseases, with increased morbidity and mortality (16,17). Pseudornonas and enterococci species have also been involved in some persistent and therapy-resistant endodontic infections (15,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…31 In order to solve this problem, laser has been introduced recently for disinfecting root canals. [32][33][34] Lasers are of different kinds and their application may lead to different results. The results of the work by Moritz et al show that performance of diode and Nd:YAG lasers for eliminating E. faecalis in pulpectomy, was better than Er:YAG laser.…”
Section: Discussionmentioning
confidence: 99%
“…17,51,52 Enterococci, which are seldom found in these circumstances, have been isolated from teeth undergoing endodontic treatment and previously root treated teeth. [53][54][55][56] In a study of root filled teeth with apical periodontitis 69% of the bacterial strains recovered from the root canals were faculative anaerobes. 53,54 Enterococci were isolated in 50% of the infective cases and were the most frequently isolated.…”
Section: Endodonticsmentioning
confidence: 99%
“…[53][54][55][56] In a study of root filled teeth with apical periodontitis 69% of the bacterial strains recovered from the root canals were faculative anaerobes. 53,54 Enterococci were isolated in 50% of the infective cases and were the most frequently isolated. A later study on the susceptibility of enterococci isolated from root canals to various antibiotics found that 25 out of 29 strains were resistant to clindamycin.…”
Section: Endodonticsmentioning
confidence: 99%